INTELLECTUAL CAPITAL AS ONE OF THE FACTORS OF DEVELOPMENT OF SOCIAL-CORPORATE TECHNOLOGIES - S. V. Ilchenko; N. D. Dmitriev; A. I. Rokov (Вестник университета)
Interaction of intellectual capital and social-corporate technologies has been studied. It has been revealed that intellectual capital management allows you to create tools, methods and mechanisms of economic and social impact on participants in corporate relations. Intellectualization of a business entity by pursuing a socially oriented policy will enable it to intensify economic activity in a social manner, improve social relations both within the company and in society, as well as affect the quality of life of people and increase the productivity of public labor. This study is a theoretical springboard for further study of the relationship between intellectual capital and social and corporate technologies, which will allow us to model the dependence, taking into account industry factors.